A biomonitoring study of Diadema setosum: metal bioaccumulation and current status in Iskenderun Bay, eastern Mediterranean - Uğurlu Erkan (Oceanological and Hydrobiological Studies)
Concentrations of aluminum, chromium, cobalt, nickel, cadmium, lead, manganese, iron and zinc were determined in sea urchin species, Diadema setosum from Iskenderun Bay in December 2022. The level of metals was determined by Inductively Coupled Plasma-Mass Spectrometer (ICP-MS). Concentrations of the heavy metals in the examined sea urchins ranged as follows: Al 0.07-7.17 μg g-1; Cr 0.07–0.8 μg g-1; Co 0.01–0.2 μg g-1; Ni 0.2–2.9 μg g-1; Cd 0.0–0.02 μg g-1; Pb 0.4-3.5 μg g-1; Mn 0.03–0.4 μg g-1; Fe 1.2-57.2 μg g-1; Zn 0.28–2.7 μg g-1, respectively. The highest accumulation of Fe and Pb metals was determined in the tissues of the sea urchin. The present study suggests that D. setosum could be a potential biological indicator of metal pollution in the Iskenderun Bay. Furthermore, soft tissues generally had lower levels overall. For this reason, the data show that D. setosum is a very good heavy metal collector and therefore may be used successfully to monitor heavy metal levels in Iskenderun Bay.